2016
DOI: 10.1097/md.0000000000003512
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between the “Chinese AMS Score” and the Lake Louise Score in the Diagnosis of Acute Mountain Sickness

Abstract: The Chinese AMS score (CAS) is used in clinical medicine and research to diagnosis acute mountain sickness (AMS). However, the Lake Louise Score (LLS) is the well-accepted standard for diagnosing AMS. The difference between the CAS and LLS questionnaires is that the CAS considers more nonspecific symptoms. The aim of the present study was to evaluate differences in AMS prevalence according to the LLS and CAS criteria. We surveyed 58 males who traveled from Chongqing (300 m) to Lhasa (3658 m) via the Qinghai-Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…However, due to the different symptoms and weights assigned, the incidence determined by the CAS assessment was higher than that by the LLS (59.3% vs 37.5%). This was consistent with previous studies [8,9]. The CAS had diagnostic accuracy for moderate and severe AMS similar to those of the LLS (16.9% vs 17.2%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, due to the different symptoms and weights assigned, the incidence determined by the CAS assessment was higher than that by the LLS (59.3% vs 37.5%). This was consistent with previous studies [8,9]. The CAS had diagnostic accuracy for moderate and severe AMS similar to those of the LLS (16.9% vs 17.2%).…”
Section: Discussionsupporting
confidence: 92%
“…[25] [26] [27] [11] Some Chinese scholars have studied the difference between the LLS and CAS in de ning AMS. Chen et al [9] surveyed 339 males residing at sea level who travelled by train and car to 3200 m. Wu et al [8] surveyed 58 males who went by train and recorded the AMS incidence when they reached different altitude sites, ending at 3658 m. They found that CAS outcomes were in good agreement with LLS outcomes and can accurately diagnose AMS, suggesting that combining the LLS and the CAS in applications of clinical diagnosis can more objectively diagnose AMS than one scoring system alone.…”
Section: Discussionmentioning
confidence: 99%
“…Untreated AMS can progress to high-altitude cerebral edema and high-altitude pulmonary edema (HAPE). 6 Approximately 140 million people, including about 79 million in Asia, live in high-altitude areas above 2,500 m. 7 These plateau residents suffer from chronic mountain sickness (CMS), a clinical syndrome that occurs in highland areas and is characterized by excessive erythrocytosis (EE) and severe hypoxemia. 8 The incidence of CMS increases with altitude and age.…”
Section: Introductionmentioning
confidence: 99%